(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The human-centric worldview permits to explore the part of the human figure in phonetics in line with inquire about destinations. This in turn puts man at the center of phonetics. The current thesis statement is based on the standards of the human-centric worldview, which analyzes the linguocultural angle of human-centric maxims, i.e., the assessment and symbolism of the human gender orientation, and outlines them with cases.